2017
DOI: 10.3390/md15060147
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Biosynthesis in a Fish Liver Cell Line (ZFL) Adapted to a Serum-Free Medium

Abstract: Although taurine has been shown to play multiple important physiological roles in teleosts, little is known about the molecular mechanisms underlying dietary requirements. Cell lines can provide useful tools for deciphering biosynthetic pathways and their regulation. However, culture media and sera contain variable taurine levels. To provide a useful cell line for the investigation of taurine homeostasis, an adult zebrafish liver cell line (ZFL) has been adapted to a taurine-free medium by gradual accommodatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…A dietary taurine level of 3.7 mg g -1 rotifer (tau1) lead to down-regulation of ado expression although the levels were not statistically different to those in fish fed tau0 or tau2. Previous studies showed no regulation of ado expression by taurine in a zebrafish cell line, which could indicate that, similar to csad and cdo, ado could be regulated post-transcriptionally (Liu et al, 2017). These results suggest that the cysteamine pathway is not very active in ABT, as has been shown for other carnivorous marine teleosts (Goto et al, 2001b).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A dietary taurine level of 3.7 mg g -1 rotifer (tau1) lead to down-regulation of ado expression although the levels were not statistically different to those in fish fed tau0 or tau2. Previous studies showed no regulation of ado expression by taurine in a zebrafish cell line, which could indicate that, similar to csad and cdo, ado could be regulated post-transcriptionally (Liu et al, 2017). These results suggest that the cysteamine pathway is not very active in ABT, as has been shown for other carnivorous marine teleosts (Goto et al, 2001b).…”
Section: Discussionsupporting
confidence: 49%
“…In addition to these enzymes, taurine transporter (Taut), a highly conserved membrane transporter is critical for the transport and recycling of taurine and plays crucial roles in intestinal functions (O'Flaherty et al, 1997;Shimizu and Satsu, 2000). Fish have varied taurine biosynthesis capability, possibly reflecting differences in the expression levels/activities of the key biosynthetic enzymes and the taurine transporter (Liu et al, 2017). For instance, Csad activity has been reported to differ among different teleost species (El-Sayed, 2014;Salze and Davis, 2015) and an apparent lack of Csad activity has been reported in fish families such as the Labridae, Scombridae and Soleidae (Salze and Davis, 2015) and ABT (Yokoyama et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The action of glutamate decarboxylases (GADs) such as GAD1 and GAD2 can synthesize gamma-aminobutyric acid, which is a neurotransmitter from amino acid glutamate ( Grone and Maruska, 2016 ). Hypotaurine could be produced involving oxidative stress and membrane damage via 2-aminoethanethiol dioxygenase oxidation ( Liu et al, 2017 ). Hypotaurine can be converted by cysteine sulfinic acid decarboxylase for taurine production ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is a metabolite that is widely distributed in animal tissues, including fish tissues [39]. Taurine is derived from cysteine and transformed by serine from the isocitrate of the TCA cycle [40]. The present study used the reprogramming metabolomics approach and iPath analysis to demonstrate TCA cycle activation and the malate-induced elevation of taurine by exogenous malate.…”
Section: Discussionmentioning
confidence: 99%